ANALISIS DAYA SAING EKSPOR KOPI INDONESIA DI PASAR DUNIA - Dhika Sulistiyo; Djeimy Kusaman; Irene Kartika Eka Wijayanti (Universitas Galuh, 2023)
This journal contains an analysis of the competitive advantages of coffee from 2015-2020 by comparing Indonesian coffee as one of the main exporting countries with several other main exporting countries such as Brazil, Colombia, Vietnam and Ethiopia. This journal uses 2 analytical tools, namely the Trade Specialization Index (ISP) and Revealed Comparative Advantage (RCA). Data collected and processed from several sources including the Badan Pusan Statistik (BPS), International Coffee Organization (ICO) and Trade Statistics for International Business Development (TradeMap). Based on the results of the analysis calculation, the Trade Specialization Index (ISP) value for Indonesian coffee commodities shows results ranging from 0 to 1. This indicates that Indonesia has competitiveness and tends to be a coffee exporting country. Based on the results of Revealed Comparative Adventage (RCA) it can be seen that Ethiopia has the highest RCA score so that Ethiopia has a comparative advantage in all periods followed by Colombia, Brazil, Vietnam. While Indonesia is ranked fifth. Indonesia has to face strong competition between Brazil and Colombia in the international market. What's more, 90% of coffee exported abroad is in the form of green coffee which is of low quality. This causes Indonesia to get lower prices compared to other countries